Aplikasi Logika Fuzzy Metode Mamdani dalam Menentukan Produksi Beras Tahun 2018 di Indones - Yulia Retno Sari (Ikatan Ahli Informatika Indonesia, 2018)
Abstract Food crops, especially rice, are important commodities. Rice as the staple food of the Indonesian people since 1950 has been increasingly irreplaceable despite the fact that the government has intensified the food diversification program. It can be seen that in 1950 the national rice consumption as a new source of carbohydrate was about 53% but in 2011 it had reached about 95%. Due to the increasing demand for rice, the supply of rice is reduced and prices are unstable. The amount of demand and supply is a matter of uncertainty. Fuzzy logic is a science that can analyze this uncertainty.The purpose of this research is to know the amount of rice production so that the related parties can determine the policy to overcome the problem of this rice. This research uses Fuzzy Application of Mamdani Method or Min-Max Method by using two linguistic variables. There are 4 stages requiered to get output of this research, they are namely; 1) Establishment of Fuzzy set; 2) Application function Implications; 3) Composition of Rules; and 4) Defuzzification. Based on this defuzzification result we can determine in making decision.